Bunuel wrote:

If a and b are constants, what is one solution of the equation (x + a)(x – b) = 0?

(1) a = 4

(2) b = 3

Statement 1

firstly when we know a= 4 then

(x+4)(x-b) = 0, now solution can be x+4= 0 or x-b = 0

x= -4 or x= b, b can be anything from - infinity to + infinity

but we know the one solution x=-4

statement 2

when b= 3

(x+a)(x-3)= 0, now solution can be x= 3 or x=-a, a can be anything from - infinity to + infinity

but we know the one solution is 3

so Option D

_________________

PS : I do mind kudos